Microelectronics, Electromagnetics and Telecommunications Proceedings of ICMEET 2015 - Satapathy, Suresh Chandra; Rao, N Bheema; Kumar, S Srinivas; Raj, C Dharma; Rao, V Malleswara; Sarma, G V K. (Lecture Notes in Electrical Engineering, 2016)
This volume contains 73 papers presented at ICMEET 2015: International Conference on Microelectronics, Electromagnetics and Telecommunications. The conference was held during 18 - 19 December, 2015 at Department of Electronics and Communication Engineering, GITAM Institute of Technology, GITAM University, Visakhapatnam, INDIA. This volume contains papers mainly focused on Antennas, Electromagnetics, Telecommunication Engineering and Low Power VLSI Design.